Design elements : a graphic style manual : understanding the rules and knowing when to break them - Samara, Timothy (Gloucester, Mass. : Rockport Publishers, 2007)
"Design Elements is a fun and comprehensive manual for graphic designers that includes hundreds of tips and examples for designers to attain the fundamental skills that contribute to successful design. It is the most compact and lucid handbook available outlining the basic principles of layout, typography, color usage, space, image, and how to put it all together. Design Elements not only offers great tips on the basics, but also shows you how to break the rules without compromising communication or confusing your audience."--Jacket.
Preface : Graphic design: what it is -- Introduction : Twenty rules for making good design -- 1. Form and space : Seeing form and space ; Categories of form ; Putting stuff into space ; Compositional strategies ; A foundation for meanings -- 2. Color fundamentals : The identity of color ; Chromatic interaction ; Color systems ; Emotions and messages -- 3. Choosing and using type ; Structure and optics ; Issues related to style ; Mechanics of text ; Texture and space ; Type as information ; How color changes type -- 4. The world of image : Real, unreal, and otherwise ; Media and methods ; Presentation options ; Content and concept -- 5. Putting it all together : Visual logic ; Structuring the page ; Intuitive arrangement ; Integrating type and image ; Layout systems -- App. A. The right design choices: twenty reminders for working designers -- App. B. Causin' some trouble: when and why to challenge anything in this book.
Keywords: Graphic design (Typography); Layout (Printing)